Experiences of Obese Adolescent Girls in Depression Prevention - Dewi, Ari Pristiana; Lipoeto, Nur Indrawati; Bachtiar, Adang; Yanis, Amel (FORIKES, 2026)
Depression in obese adolescent girls is a serious disorder that can affect their behavior, emotions, and thoughts. The purpose of this study was to explore the experiences of obese adolescent girls in preventing depression. This study used a qualitative approach, a phenomenological study. The participants were 11 obese adolescent girls in Pekanbaru City, selected using a purposive sampling technique. The data collection method used was in-depth interviews. Data were analyzed using the Colaizzi method. The results showed that there were four themes and 13 sub-themes. The first theme was the unpleasant experiences of obese adolescents, consisting of three sub-themes: body shaming, bullying, and discrimination. The second was the psychological impact, consisting of two sub-themes: intrapersonal and interpersonal impacts. The third was the internal factors determining depression prevention, consisting of four sub-themes: knowledge of depression, self-esteem, self-image, and coping mechanisms. The fourth was the external factors determining depression prevention, consisting of four sub-themes: peers, teachers, family, and health care workers. In conclusion, obese adolescent girls had unpleasant experiences, experienced psychological impacts, and were aware of the internal and external determinants of depression prevention. It is hoped that healthcare institutions will provide intensive nursing care for adolescents with obesity to prevent depression.Keywords: adolescent girls; obesity; depression; experience; prevention